Adobe Acrobat 6 PDF for Dummies - Harvey, Greg (Wiley Publishing, 2011)
Covers accessing and distilling PDF files; converting Microsoft Office documents; capturing paper documents and Web pages; printing, annotating, editing and securing PDF files; extracting text and graphics; cataloging and distributing PDF files; creating interactive forms; and building multimedia presentations.